Mastering Windows server 2003 Upgrade Edition for SP1 and R2 - Minasi, Mark (Wiley, 2006)
The In-depth Coverage You've Been Waiting for on SP1 and R2 Picking up where Mastering Windows Server 2003 left off, bestselling author and leadingWindows Server expert Mark Minasi returns with a much-anticipated Upgrade Edition that delivers exactly the information you need to understand SP1 and R2.